Retos y desafíos para las empresas en la cuarta revolución industrial (2022)
The present bibliographic review allowed to analyze the challenges that companies have in the Fourth Industrial Revolution, through which it was possible to inquire about the economic, social and political context that this new technological era entails and how traditional companies can enter in this new digital context. For this, an exhaustive search of recent research related to the subject is made, in order to theoretically validate the aspects dealt with in the monograph, emphasizing the importance of new technologies and the optimization in production that it means for companies. the Revolution 4.0. Fundamental aspects of the large companies that have been successful in this new context of digitization and the aspects that must be followed by companies that want to solve the challenges that arise are analyzed. In addition, the relevance of marketing online is emphasized, but it is also important to maintain physical marketing or through traditional channels, that is, to have business digitization as an alternative or support for the industrial growth of companies.